Mechanisms of Oogenesis-Related Long Non-coding RNAs in Porcine Ovaries Treated With Recombinant Pig Follicle-Stimulating Hormone - Mao, Haiguang; Chen, Lu; Bao, Rupo; Weng, Shiqiao; Wang, Mengting; Xu, Ningying; Qi, Lili; Wang, Jinbo (Frontiers in Veterinary Science, 2022)
Reproductive efficiency is of significant importance in pork production for it has a great impact on economic success. Ovulation rate is an early component of reproduction efficiency of pigs and it contributes to the upper limit of litter size. In this study, we used the newly developed recombinant pig follicle stimulating hormone (rpFSH) instead of traditional PMSG to increase ovulation rate of pigs in order to achieve higher litter size, for it is better at stimulating ovulation, and shows more cheaper and greener. However, relatively little is known about the underlying genetic bases and molecular mechanisms. Consequently, an experiment was carried out in ovaries of replacement gilts to screen the key genes and lncRNAs that affect the fecundity of pigs by RNA-seq technology. Twenty gilts divided into two groups, including 10 rpFSH treatment pigs and 10 control animals. After slaughtering and collecting the phenotypic data, ovaries of 5 pigs in each group were selected for RNA-seq. Total RNA was extracted to construct the library and then sequence on an Illumina Hiseq 4000 system. A comprehensive analysis of mRNAs and long noncoding RNAs (lncRNAs) from10 samples was performed. with bioinformatics. The phenotypic data showed that rpFSH treatment groups had the higher (P < 0.01) ovarian weight and more mature follicles. The RNA-seq results showed a total of 43499 mRNAs and 21703 lncRNAs were identified, including 21300 novel lncRNAs and 403 known lncRNAs, of which 585 mRNAs and 398 lncRNAs (P<0.05) were significantly differentially expressed (DE) between the two groups of rpFSH treatment group and controlled group. GO and KEGG annotation analysis indicated that the target genes of DE lncRNAs and DE mRNAs were related to prolactin receptor activity, mitophagy by induced vacuole formation and meiotic spindle. Moreover, we found that NR5A2 (nuclear receptor subfamily 5, group A, member 2), a target gene of lncRNA MSTRG.3902.1, was involved in regulating follicular development, ovulation and estrogen production. Our study provided a catalogue of lncRNAs and mRNAs associated with ovulation of rpFSH treatment, and they deserve further study to deepen the understanding of biological processes in the regulation of ovaries of rpFSH treatment pigs.